The Ventricular System Enlarges Abnormally in the Seventies, Earlier in Men, and First in the Frontal Horn: A Study Based on More Than 3,000 Scans - Currà, Antonio; Pierelli, Francesco; Gasbarrone, Riccardo; Mannarelli, Daniela; Nofroni, Italo; Matone, Vittoria; Marinelli, Lucio; Trompetto, Carlo; Fattapposta, Francesco; Missori, Paolo (Frontiers in Aging Neuroscience, 2019)
OBJECTIVES: To detect on computed tomography (CT) brain scans the trajectories of normal and abnormal ventricular enlargement during aging. METHODS: For each one-year age cohort, we assessed in 3193 axial CT scans the Evans’ index (EI) in the anterior frontal horns and the parieto-occipital (POR) and temporal ratio (TR) in the posterior and inferior horns. Cut-off values for abnormal enlargement were based on previous clinical studies. RESULTS: The mean age associated with normal linear measures was 71 years. Values for all three measures increased with age, showing a linear relationship below – but not above – each cut-off value. The mean age of participants with abnormal enlargement on CT progressed from 79 years for EI to 83 years for POR to 87 years for TR. These results suggested that ventricular dilatation progresses in an age–location relationship. First comes enlargement of the frontal horns (13.8% of scans), followed by the parieto-occipital horns (15.1% of scans) and then temporal horn enlargement (6.8% of scans). Scans from men displayed abnormal values earlier than scans from women (on average 6 years). Risk increased 5.1% annually for abnormal EI, 9.0% for abnormal POR, and 11% for abnormal TR (all p<0.001). The most frequent agreement between categories (normal–abnormal) for values of neuroimaging measures was identified for POR–TR. CONCLUSION: The results of this large radiological study suggest that the ventricular system enlarges progressively during aging, and in a subset of patients follows an abnormal consecutive geometric dilatation, influenced by age and sex.